Nitrogen-Doped TiO2 Photocatalyst Prepared by Mechanochemical Method: Doping Mechanisms and Visible Photoactivity of Pollutant Degradation - Yu-Chao Tang; Xian-Huai Huang; Han-Qing Yu; Li-Hua Tang (International Journal of Photoenergy)
Nitrogen-doped TiO2 (N/TiO2) photocatalysts were prepared using a mechanochemical method with raw amorphous TiO2 as precursors and various nitrogenous compounds doses (NH4F, NH4HCO3, NH3·H2O, NH4COOCH3, and CH4N2O). The photocatalysts were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), thermal gravimetric-differential thermal analysis (TG-DTA), and UV-Vis diffuse reflection spectra (UV-Vis-DRS). Their photocatalytic activities were evaluated with the degradation of p-nitrophenol and methyl orange under UV or sunlight irradiation. The catalysts had a strong visible light absorption which correspond to doped nitrogen and consequent oxygen deficient. The results of photocatalytic activity showed the visible light adsorption mechanisms, as the doped nitrogen species gave rise to a mid-gap level slightly above the top of the (O-2p) valence band, but not from the mixed band gap of the N-2p and O-2p electronic levels.